Konsepsi Manajemen Perubahan - Anggraini, Siti (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2008)
All institutions live and perform in two  time periods: :  today and tomorrow. Tomorrow is being made today-irevocably in most cases. In turbulent times managers can not assume that tomorrow will be an extensionof today.  On the contrary, they must manage of  "change" as an opportunity and change as a treat.